Asuhan Keperawatan Pada Keluarga Tn.H Dengan Masalah Diabetes Melitus Pada Ny.S Di Desa Tegalrejo B Kartasura, Sukoharjo - Nurmalita, Mei; , H.M. Abi Muhlisin, SKM., M.Kep (2015)
Background: Diabetes mellitus is a metabolic disorder that genetically and clinically belong heterogeneous with manifestations such as increase in blood sugar levels due to insulin deficiency both in absolute and relative. Diabetes mellitus often occurs in people who are elderly or in people who havethe same descenthistory. Data in Community Health Center of Kartasura showed that in January to April 2015 there were 493 cases of diabetes mellitus visits recorded. 122 cases were old cases, whilst the rest 371 cases were new cases. The prevalence is almost the same between female and malepatients. Objective: To determine the nursing care of families with a major problem in diabetes mellitus includes assessment, diagnosis enforcement, intervention, implementation, and nursing evaluation. Results: After nursing care for four days in four home visitations: one hour per visit showed increased family knowledge about the disease, imbalancenutrition: less than body requirements can be resolved, and no complications from the disease, modify the environment and also utilize the health care. Conclusion: Cooperation among health workers, clients and family are indispensable for the success of familynursing care. Therapeutic communication can encourage clients and families to be more cooperative. Health education can broaden the client and family's knowledge about the disease and diabetic foot gymnasticscan prevent, provide a sense of comfort, and also improve blood circulation in order to avoid complications. Keywords: diabetes mellitus, imbalance nutrition: less than body requirements, complications risk.